Centro de acolhimento : intervenção para a afirmação do direito de cidadania da criança e da família - Vieira, Sandra Regina Alexandre Ferreira, 1973- (1998)
Intervenção social. - ISSN 0874-1611. - N. 17-18 (1998). - p. 69-83